MODIFIKASI MESIN SPINNER PENIRIS MINYAK DENGAN MENAMBAHKAN TIMER DIGITAL - Jamaluddin Jamaluddin; Muh Wahyu Asyfan; Andi Haslinah (ILTEK : Jurnal Teknologi, 2026)
The oil spinner machine is a device that works based on the principle of centrifugal force to reduce the oil content in fried products. The use of conventional spinner machines still has weaknesses, especially in terms of drainage time settings, which are not yet automatically controlled, making them less efficient and consistent. Therefore, this study aims to modify the oil spinner machine by adding a digital timer system to improve time efficiency and spinning performance. The research methods used include the design, manufacture, assembly, and testing stages of the machine. The machine was modified by adding a digital timer as a spinning time control system integrated with an electric motor. Testing was conducted using fish floss with varying weights of 500 grams, 1000 grams, and 1500 grams. The parameters observed included the drying time and the weight of the material before and after the drying process. The test results showed that the addition of a digital timer was able to control the drying time automatically and consistently. The average drainage time for a capacity of 500 grams was 6 minutes and 10 seconds with a final weight of 375 grams, a capacity of 1000 grams for 9 minutes and 30 seconds with a final weight of 750 grams, and a capacity of 1500 grams for 13 minutes and 15 seconds with a final weight of 1010 grams. This shows that the modified spinner machine is capable of effectively reducing oil content and improving the efficiency of the draining process. Thus, it can be concluded that modifying the oil draining spinner machine by adding a digital timer improves performance, ease of operation, and time efficiency, making it suitable for use in households and small to medium-sized businesses.